Communication through questions: A corpus-based study of questions posed by lecturers - Živković, Branka (Círculo de Lingüística Aplicada a la Comunicación, 2022)
Few previous studies have focused on the analysis of the use of questions in academic university lectures delivered in English. However, the issue of the forms and role of questions in Montenegrin lectures has received no research attention. The current study explores the forms and functions of questions posed by lecturers in Montenegrin academic lectures. The analysis is based on a specially created corpus of Montenegrin lectures on linguistics and applies both quantitative and qualitative methodologies. The questions most frequently found in these lectures have been classified into categories in terms of their function, followed by the detailed analysis of their most common formal realisations. The variation in frequency of the functional categories, as well as in their questioning forms, has been revealed. The findings provide new insights into certain types and role of questions.